IOC: Merangsang Minat Belajar Siswa SD - Syawal, Sahrul; Tulak, Harmelia; Ishak, Suryadi; Wajdi, Fathullah; Rante, Susanna Vonny N.; Tulak, Topanus (Elementary Journal : Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This study seeks to examine the implementation of the IOC Learning Model (Inside-outside-circle) in enhancing the interest and academic performance of elementary school children. This model emphasizes the interconnection of learning inputs, instructional processes, and learning outcomes, while taking into account the educational environment's context. This research used a literature review methodology, examining the efficacy of the IOC Model across diverse educational settings. The findings indicate that the IOC Model can provide a more pertinent and stimulating educational experience, particularly in primary education. It is adaptable and attuned to the diverse individual requirements of students, hence fostering intrinsic drive and critical thinking abilities. The effective execution of the IOC Model is contingent upon teacher preparedness, educational infrastructure, and sufficient policy backing. This study indicates the necessity for additional empirical research to evaluate the model's performance across many educational contexts and to discern the difficulties and opportunities associated with its implementation. The IOC model possesses the capacity to enhance educational quality, particularly in addressing the problems of 21st-century learning.